Turkish Translation of Ibnu'l Hâjib's Al-Kâfiye (Manzûm Kâfiye Mefhûmu) - Eren Ertürkoğlu (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Since the beginning of the educational activities in madrasahs, the teaching of linguistic sciences and religious sciences has been of great importance. This is because in order to learn religious sciences, it is necessary to understand Arabic. this regard, linguistic sciences, such as sarf (morphology), nahiv (syntax) and lugat (lexicography) have always been taught. Among them, syntax has been given significant importance. In particular, Al-Kâfiya, a work frequently taught in Ottoman madrasahs, has made the syntax topics more concise and simple. Among the translations of this work are the verse and prose ones. A verse translation of a scientific work can have many reasons both for the translator him/herself and for the target audience. However, the general trend on this subject is that verse works are easier to learn, easier to repeat, and they have a higher memorization potential. Thus, this study examines and transcribes Ibn al-Hâjib’s al-Kâfiya and his verse translation by Şâkir (one of the 18th century poets), and focuses on the reasons for translating this syntax work.